2018
DOI: 10.1016/j.freeradbiomed.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Insight into ultrasound-mediated reactive oxygen species generation by various metal-porphyrin complexes

Abstract: Ultrasound is used to trigger the cytotoxicity of chemical compounds, known as sonosensitisers, in an approach called sonodynamic therapy (SDT), which is under investigation herein. The generation of reactive oxygen species (ROS) has been proposed as the main biological occurrence that leads to the cytotoxic effects, which are achieved via the synergistic action of two components: the energy-absorbing sonosensitiser and ultrasound (US), which are both harmless per se. Despite some promising results, a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 70 publications
1
57
0
Order By: Relevance
“…Use of ultrasound with lower frequency and power improves the cavitation and concomitant biological effect (Hu et al, ; Qian, Zheng, & Chen, ). Multiple studies have shown that some sensitizers can be efficiently activated by ultrasound and generates cytotoxic ROS (Giuntini et al, ; Li et al, ; Rwei et al, ). Recently, a lot of sonosensitizers has been applied in SDT, including TiO 2 , chlorin, phthalocyanines and photofrin (Osaki et al, ; Rwei et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of ultrasound with lower frequency and power improves the cavitation and concomitant biological effect (Hu et al, ; Qian, Zheng, & Chen, ). Multiple studies have shown that some sensitizers can be efficiently activated by ultrasound and generates cytotoxic ROS (Giuntini et al, ; Li et al, ; Rwei et al, ). Recently, a lot of sonosensitizers has been applied in SDT, including TiO 2 , chlorin, phthalocyanines and photofrin (Osaki et al, ; Rwei et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently some researchers have suggested US as a new tool to overcome certain drawbacks and improve the light delivery, mainly in the field of PDT and optogenetics. 5,[23][24][25][26][27] Light from sound…”
Section: Application Of Light In Medicinementioning
confidence: 99%
“…Sonoluminescence can be observed as occurring after stimulation in the ultrasonic frequency range, from 20 kHz up to 3 MHz, and is influenced by acoustic pressure, frequency, liquid proprieties, temperature and specific gas content. 19 The sonosensitizer activation is made feasible through the emission of sonoluminescent light over a broad range encompassing the Soret band of many porphyrin sonosensitizers as demonstrated by Umemura et al 15 . Sonoluminescence was recently observed by Giuntini et al 19 , studing the ultrasound-mediated various metal-porphyrin complexes activation.…”
Section: Sonophysics and Sonochemistry Process In Sdtmentioning
confidence: 99%
“…19 The sonosensitizer activation is made feasible through the emission of sonoluminescent light over a broad range encompassing the Soret band of many porphyrin sonosensitizers as demonstrated by Umemura et al 15 . Sonoluminescence was recently observed by Giuntini et al 19 , studing the ultrasound-mediated various metal-porphyrin complexes activation. Alternatively, pyrolysis of sonosensitizers may be the source of ROS generation following SDT.…”
Section: Sonophysics and Sonochemistry Process In Sdtmentioning
confidence: 99%
See 1 more Smart Citation